Development of a Web-based learning tool for undergraduate health professionals studying applied anatomy - Valerie Cooper; Mike McConnell (Association for Learning Technology, 2000)
It is a commonly accepted maxim of education that independent learning and directed study accommodate individual learning styles and allow students to acquire basic facts and principles. Such practices are increasingly desirable in the current educational climate as they allow teaching staff to use valuable contact time to address higher cognitive skills. However, when there is a requirement for such learning to be practice-based it is not always possible to provide students with the necessary resources for independent study.